Critique of the living dead: algorithmic aesthetic and the biopolitics of the zombie - Juan J. Vargas-Iglesias (Journal of Aesthetics & Culture, 2022)
Recognizing the importance of the zombie in the interpretative forms of contemporaneity, this paper aims to actualize the current focus of the phenomenon in order to understand it within a strictly material framework. Its aim therewith is to take the perception of the zombie, not as a symptom or metaphor as commonly done, but as a floating signifier in order to analyze the material conditions that allow it to be understood as a symptom or metaphor. To this end, an observation from the perspective of Gothic Materialism is stated, attending to the implications of the idea of “nonorganic life” in the reshaping of human reality and posing both focuses of the approach, the post-structuralist and the materialist, on the basis of their Deleuzian inspiration. The final purpose is to provide an epistemological ground for the comprehension of this cultural motif of the ominous in biopolitical and aesthetic terms, by means of a comparative analysis of videoludic cases with others in film media.